Sustainability Marketing for Gen Z Consumers: The Role of Functional, Emotional, and Social Value on Satisfaction and Purchase Intention in Surabaya - Janice Carysa Siahaya; Priskilla E.E. Napitupulu; Yanuar Dananjaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study examines the influence of functional value, emotional value, and social value on satisfaction and purchase intention toward reusable smart tumblers among Gen Z in Surabaya. Using a quantitative approach, data were collected from 250 respondents and analyzed with multiple regression. The results show that all three values significantly and positively affect satisfaction, and satisfaction significantly drives purchase intention. These findings highlight that Gen Z purchase decisions are shaped not only by product functionality but also by emotional attachment and social recognition related to sustainability. This study provides insights for marketers to enhance consumer satisfaction and strengthen purchase intention through sustainability-based strategies.